The Influence of Customer Relationship Management and Customer Experience on Customer Satisfaction - Suharto suharto; yuliansyah yuliansyah (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This research attempts to examine how customer relationship management and customer experience influence customer satisfaction in Lampung Province retail complexes. Data was taken using non-random sampling method with purposive sampling technique and used to meet the number of samples as many as 135 respondents. Validity, reliability, construct reliability, and variance extraction were used to evaluate the quality of the data. Prior to data analysis, the Liliefors normal requirements, homogeneity, linearity, and significance of regression were examined. Structural Equation Modeling is a structural equation used to analyze the model. The research findings are that there is a direct positive effect of customer relationship management on customer experience, customer relationships have a direct positive effect on customer satisfaction, and customer experience has a direct positive effect on customer satisfaction